Development and full-scale validation of high-fidelity data acquisition on a next-generation wireless smart sensor platform. Issue 16 (December 2019) - Fu, Yuguang; Mechitov, Kirill; Hoang, Tu; Kim, Jong R; Lee, Deuck Hang; Spencer, Billie F
Although wireless smart sensor platforms have been available over a decade, only a limited number of full-scale wireless smart sensor–based structural health monitoring implementations have been realized. Most wireless smart sensor platforms that are validated in full-scale implementations have now become obsolete and are no longer commercially available. While wireless sensing capabilities have grown, presenting significant opportunities, obstacles to wide application of wireless smart sensor for structural health monitoring exist both in terms of hardware and software. This article assesses the efficacy of the Xnode, a new wireless platform whose development has been driven by structural health monitoring requirements, as well as lessons learned from several full-scale wireless smart sensor deployments. The capabilities of the platform are evaluated in comparison with other commercial wireless smart sensors, in terms of hardware, software, and mechanical design. Extensive laboratory and field testing is employed to validate its performance on three aspects: fidelity of data acquisition, reliability of wireless communication, and efficiency of power management. Test results demonstrate the capabilities of the Xnode to support full-scale, high-fidelity data acquisition for civil infrastructure. In addition, the new sensor platform provides several significant benefits to extend the use of wireless smart sensors to a broader class of structural health monitoring applications, such as sudden event monitoring and real-time and control applications.